EFL Teacher Professional Development Needs: Voices from the Periphery - Marta Isabel Barrientos-Moncada; Natalia Andrea Carvajal-Castaño; Hernán Santiago Aristizabal-Cardona (Asociación Colombiana de Profesores de Ingles, 2023)
EFL teachers' professional development in Colombia has been characterized by top-down policies that neglect the regions in terms of contextualized professional development programs and resources. This article is an effort to make EFL teachers' needs in the Eastern region of Antioquia, Colombia, visible for academic institutions and local authorities to propose coherent professional development programs. This report is based on a section of the findings of a larger study called "Diagnosis of the needs about plurilingualism in the regions of Antioquia". Findings show that EFL teachers in the Eastern region claim for ongoing and contextualized professional development programs, differentiated for primary and secondary-school teachers, and focused on instructional material design and adaptation according to the resources available in the local communities. Conclusions from this study outline implications for educational institutions to support teachers in pursuing their professional development within their contexts, methodological limitations for researchers, and possibilities for further research for stakeholders in the territory.